The Relationship of Transformational Leadership and Organizational Commitment in Higher Education - Rojak, Jeje Abdul (Bulletin of Science, Technology and Society, 2024)
This study explores the relationship between transformational leadership and organizational commitment in higher education. Correlational research methods were used with 54 staff as respondents. This study aims to assess the effectiveness of Green Human Resource Management (GHRM) in enhancing organizational performance. Using a literature review method, it examines key GHRM practices such as green recruitment, environmental training, performance management, and sustainability-oriented culture. The analysis results show a significant positive correlation between transformational leadership and organizational commitment. This confirms that the higher the level of transformational leadership, the higher the level of organizational commitment. These findings are consistent with previous research that highlights the important role of leadership in forming organizational commitment. The practical implication of this research is the need to develop more effective leadership strategies in higher education to increase organizational commitment. Although these findings provide important contributions, this study has limitations in sample size and research design. Future studies could expand the sample scope and explore other factors that influence this relationship.